An Overview of Hydrogen Prospects: Economic, Technical and Policy Considerations - Aguilera, Roberto F.; Inchauspe, Julian (Australian Agricultural Economics Society, 2021)
Hydrogen is expected to play a role in the future low-carbon economy as an energy carrier, but its market penetration remains to be seen. Much of the existing literature generally focusses on comparison of marginal production costs and prices to make rather optimistic projections. This study argues that such analysis is myopic as important barriers are ignored. Following a Porter’s five-force approach, we methodologically identify the economic market forces that shape the development of hydrogen markets, and discuss key obstacles in the supply chain. Using evidence of available hydrogen technologies and costs, the distribution network is identified as a major fixed-investment barrier to market entry, but it is argued that much of it could be overcome if natural gas infrastructure and technology is shared with the hydrogen sector. Natural gas, in turn, is projected to function as a transition fuel under current carbon emissions targets. This study finds that policy costs needed to promote hydrogen to achieve environmental goals can be substantially reduced if government and private investment decisions strategically focus on synergies with natural gas. The possible formulation of such policies is discussed at a lower level using Australia’s hydrogen industry as a case study.